La forma in movimento: Il corpo dell'attore nella tradizione scoliastica: una prima indagine - Marinelli, Manlio (2024)
This paper analyzes and aims to highlight the gestures and bodily strategies of the tragic actor as the scholia describe them to the reader. According to them, tragic actors used strategies and patterns that not only had semantic valences but also brought into play specific skills to provoke the emotions of spectators. The article aims to argue that Hellenistic scholars observed the performers' bodily strategies without prejudice regarding the actors' dominance in achieving tragic effects. Certainly, it must be kept in mind that these sources deal with performances dating back to the fifth century: the memory of ancient scholarship is part of the way in which the tragic phenomenon is considered. This article is not about performance but about its memory.